2012
DOI: 10.1172/jci61134
|View full text |Cite
|
Sign up to set email alerts
|

Mouse and computational models link Mlc2v dephosphorylation to altered myosin kinetics in early cardiac disease

Abstract: Actin-myosin interactions provide the driving force underlying each heartbeat. The current view is that actinbound regulatory proteins play a dominant role in the activation of calcium-dependent cardiac muscle contraction. In contrast, the relevance and nature of regulation by myosin regulatory proteins (for example, myosin light chain-2 [MLC2]) in cardiac muscle remain poorly understood. By integrating gene-targeted mouse and computational models, we have identified an indispensable role for ventricular Mlc2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
196
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(208 citation statements)
references
References 53 publications
10
196
2
Order By: Relevance
“…We used a computational model of myocyte shortening (26,27) to explore the mechanisms that would explain the paradox of the cardiomyocyte calcium transient and cell shortening data. We first constructed idealized calcium transients (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We used a computational model of myocyte shortening (26,27) to explore the mechanisms that would explain the paradox of the cardiomyocyte calcium transient and cell shortening data. We first constructed idealized calcium transients (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…31 The downregulation of cardiac MLCK decreases the steady-state levels of MLC2 phosphorylated; therefore, it was proposed to be the main myosin kinase acting on cardiac myocytes. 31,32 Decreased levels of phosphorylated MLC2-P have been observed in HF. 33 In addition, these studies demonstrated a global decrease of myofilament protein phosphorylation occurring during HF.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of Ser15 has been recognized to play an important role in cardiac muscle contraction under normal and disease conditions (9). Significantly reduced RLC phosphorylation was reported in patients with heart failure (10, 11) and observed in animal models of cardiac disease (5, [12][13][14]. Attenuation of RLC phosphorylation in cardiac MLCK knockout mice led to ventricular myocyte hypertrophy, with histological evidence of necrosis and fibrosis, and to mild dilated cardiomyopathy (15,16).…”
mentioning
confidence: 99%